Paparan Debu Total Pada Pekerja Produksi Terhadap Penyakit Akibat Kerja di PT Wijaya Karya Beton Tbk. Pasuruan - Faisal Al Farisi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Dust exposure in the concrete industry is one of the major occupational health risk factors, particularly related to respiratory disorders among workers. Total dust containing fine particles can enter the respiratory system and lead to various health issues, ranging from mild irritation to chronic obstructive pulmonary disease (COPD) over the long term. This study aims to analyze the level of total dust exposure among production workers at PT Wijaya Karya Beton Tbk. and evaluate the effectiveness of the control measures implemented. The research method involved measuring total dust concentrations in several production areas and comparing the results with the Threshold Limit Value (TLV) established in the Indonesian Ministry of Manpower Regulation No. 5 of 2018. The findings indicate that the measured total dust levels remain below the allowable limit (<10 mg/m³). However, preventive actions are still necessary to ensure a healthy and safe work environment. Control efforts such as natural ventilation, water spraying, and the use of protective masks have been implemented by the company. Nevertheless, regular monitoring and further evaluation are required to enhance the effectiveness of worker protection. This study highlights the importance of consistently applying occupational safety and health (OSH) systems and emphasizes the need for education and training for workers regarding dust exposure risks and appropriate preventive measures.